Current Distribution of a Luxurious Wood Species, Diospyros spp. with Its Climatic Information, based on Global Biodiversity Website - Eko Prasetyo; Singgih Utomo; Ahdiar Fikri Maulana; Ridla Arifriana; Puji Lestari (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Ebony (Diospyros spp.) is a fancy wood distributed in eastern Indonesia. D. celebica Bakh, D. lolin Bakh, D. pilosanthera Blanco, D. ebenum Koenig, D. ferrea (Wild.) Bakh and D. rumphii Bakh are categorized as